Halpern-type proximal point algorithm in CAT(0) spaces - Okeke, Chibueze Christian (Topological Methods in Nonlinear Analysis, 2023)
A method which is a combination of the Halpern method and proximal point method (PPA) is introduced in this paper. It is proved that the sequence of iterates generated by our method converges strongly to a point which is a common solution to some monotone inclusion problem and fixed point problem in CAT(0) spaces under some appropriate conditions.